Past, present and future: a look at the history of the euphonium as a solo instrument through a master's euphonium recital and program notes - Horne, Joseph Richard (My University, 2026)
This report will examine repertoire selected for a master's euphonium recital using literature written in the instrument's past and present. Consideration will be given as to what the role of the euphonium will be in the future, and how its body of literature will be reflected. It will also be a discussion of the composers who have written these selections, the context in which they exist, and a pedagogical study of each piece will comprise each chapter to give the reader a comprehensive knowledge of the recital program. Chapter one will examine Amilcare Ponchielli's Concerto per Flicornobasso, a nineteenth-century work that has become a staple in the euphonium repertoire. Chapter two will examine the first movement of Vladimir Cosma's Euphonium Concerto, Allegro Assai. This work is regarded by many as the pinnacle of modern concerti written for the euphonium. Chapter three will examine the first and fourth movement of Ralph Sauer's transcription of Johann Sebastian Bach's Gamba Sonata No. 1, BWV 1027. It will include a discussion on working towards a historically informed performance according to Baroque-era practices. Chapter four will examine Wild Geese by Grace Bergstrom, a piece originally written for tuba and fixed media that is completely improvised by the performer. Chapter five will examine Cubes by Eduardo Nogueroles, a five-movement work written for tuba quartet based on the paintings of Pablo Picasso. This recital was performed on Thursday, March 26, 2026 at 6:15pm at All-Faiths Chapel in Manhattan, Kansas.
Keywords: Euphonium; Amilcare Ponchielli; Vladimir Cosma; J.S. Bach; Grace Bergstrom; Eduardo Nogueroles